Linear amplicons as precursors of amplified circles in methotrexate-resistant Leishmania tarentolae. - Grondin, K (1998)
Gene amplification is frequently observed in Leishmania cells selected for drug resistance. By gene targeting we have tagged both alleles of the H locus of Leishmania tarentolae with the neomycin and hygromycin phosphotransferase genes ( neo and hyg ). Selection of these recombinant parasites for low level methotrexate resistance led to amplification of the H locus as part of linear amplicons. The availability of tags has permitted us to determine that both alleles can be amplified in the same cell and that chromosomal deletions are frequent. When methotrexate concentration was increased in subsequent selection steps, circles were observed in several mutants. We have introduced a hyg marker into linear amplicons to test whether the circles originated from linear amplicons. After selection with a high methotrexate concentration, circles with the hyg marker were observed, showing that circles can indeed be formed from linear amplicons. The tagging of H locus alleles permits appreciation of the extent of genetic rearrangements leading to amplicon formation in Leishmania cells selected for drug resistance.